EMERGING NEED OF PHARMACOKINETICS IN DEMYSTIFICATION OF HERBO-MINERAL COMPOUNDS (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda has its own way of processing herbal, mineral, metallic and animal origin materials to prepare therapeutic dosage forms. Pharmacology is the science of drugs including their origin, composition, pharmacokinetics, therapeutic use, and toxicology.  Pharmacology is the base of research and development in all medical sciences which utilizes natural or synthetic materials for therapeutic purposes and such materials as known as medicines. Importance of Pharmacokinetics in Ayurveda: It is evident that understanding of pharmacokinetic characteristic especially bioavailability of Ayurveda drug compounds is needed while planning as well as interpreting the result of experimental/clinical studies. Challenges to Herbo-mineral compounds: Several experiments as well as clinical researches regarding safety profile of Rasoushadhi have been conducted at various Ayurveda institutes at graduate and post graduate level, however these researches have not attracted the attention on global platform. Conclusion: Pharmacokinetic studies will be helpful in discovery of Ayurveda drug action, organ involved, safety studies, dose determination, ADME of AYUSH medicines, information of bioavailability, mode of action, identifing differences in Ayurveda drugs having similar chemical composition.